Comparable outcome of stem cell transplant versus bortezomib-based consolidation in myeloma patients after major response to induction. (1st November 2013) - Gao, Wen; Geng, Chuanying; Zhang, Lei; Li, Yanchen; Chen, Wenming; Wang, Chen
<x xml:space="preserve">Abstract</x> High-dose therapy with autologous stem cell transplant (ASCT) has been established as standard treatment for eligible patients with myeloma. However, whether this approach is still beneficial with new therapy is yet to be determined. Consolidation of effective therapy may be an alternative to ASCT following major response to initial induction. This retrospective case-series analysis included a total of 48 patients with newly diagnosed myeloma. All these patients achieved complete response or very good partial response to bortezomib-based induction and were eligible for ASCT; 24 of these patients proceeded with ASCT, and other 24 patients opted out of ASCT and received two additional cycles of bortezomib therapy as consolidation. With a median follow-up of 28.5 months in ASCT group and 29 months in non-ASCT group, no significant difference was seen in progression-free survival, 39 versus 32 months, P = 0.82. Median overall survival had not been reached, and the estimated 3-year overall survival rates were 87.5 and 67.5% in ASCT and non-ASCT, respectively, P = 0.97. This study provides an initial assessment of survival outcome of ASCT in comparison with non-ASCT consolidation. The additional study is required to establish the efficacy of non-ASCT consolidation.